Prevalence & Risk Factors of Anxiety and Depression among Cases of Hyperemesis Gravidarum - Elgathafi , Aziza; Elharary , Fawzia; Al Shawbaki, Muna; Boubataina , Heba (Scientific Journal of University of Benghazi, 2023)
Background: Hyperemesis gravidarum (HG) is a sever nausea and vomiting before 22nd week of Gestation. Antenatal depression and anxiety become a common problem significantly affecting maternal and fetal health, there is a complex relation between anxiety and depression and hyperemesis gravidarum. The aim: is to identify and study the prevalence of anxiety and depression and their related risk factors for hyperemesis gravidarum(HG) cases. Subject and methods: A descriptive, cross-sectional study was conducted at the Benghazi Medical Center (BMC) on cases diagnosed with HG and admitted to the Gynecology Department in the period between 1-10-2019 and 31-3-2021. Data was collected through direct interviews with women and using the Hospital Anxiety and Depression Scale (HADS) with some data collected from their medical records. The data was analyzed using SPSS Ver. 23. The statistics used were descriptive; frequencies, mean, standard deviation and median as well as inferential; chi-square test, one-way ANOVA and t-test. P<0.05 is used to denote statistical significance. Results: High anxiety levels were found in 76.4% and high depression levels were noted in 82% of cases. From the value of the adjusted odd ratio, women with Libyan nationality are strongly associated with high anxiety (5, 95% CI: 1.021-1.284), followed by a positive history of hyperemesis in previous pregnancies (3.375, 95% CI: 1.161-9.809) and a higher maternal age (1.14, 95% CI: 1.021-1.284). Regarding maternal education and pregnancy planning, it has been found that these factors are protective against high anxiety. After adjustment by using multivariable logistic regression, only a history of hyperemesis in previous pregnancies was identified as an independent risk factor for high depression among the cases (AOR, 3.167 95% CI: 1.005-9.979). Conclusion: High levels of both depression and anxiety were recorded among cases of hyperemesis at the Benghazi Medical Centre.